Design and Evaluation of a Reliable Automated ECU Reprogramming Framework - Phaninthara Sunthonmani; Poom Konghuayrob; Warachart Suwan-Ngam (My University, 2025)
Reliable reprogramming of Electronic Control Units (ECUs) is vital for safety and functional integrity in modern vehicles. Manual flashing methods remain prone to human errors, inconsistent outcomes, and scalability issues. This research introduces an automated ECU flashing or reprogramming framework using the Vector Toolchain, combining Flash Pack automation with Unified Diagnostic Services (UDS) routines to ensure structured and repeatable processes. Large-scale experiments across multiple ECUs were conducted to assess robustness, error recovery, execution time, and scalability, supported by comprehensive logging and automated reporting for traceability. Experiments on multiple ECUs show reduced errors, faster execution, and improved scalability with success rate more than 80%. The proposed approach enhances reliability and reproducibility in large-scale as well as provides methodological insights and foundation flashing issue analysis for future research.
Keywords: Embedded Systems Design Techniques; Formal Methods in Verification; VLSI and Analog Circuit Testing